Writing Clearly : ECB's Monetary Policy Communication - Cihak, Martin (IMF Working Papers; Working Paper, 2008)
The paper presents a methodology for measuring the clarity of central bank communication, illustrating it with the case of the European Central Bank (ECB) in 1999-2007. The analysis identifies the ECB's written communication as clear about 95 percent of instances, which is comparable to, or even better than, other central banks for which a similar analysis is available. We also find that the additional information contained in the ECB's Monthly Bulletins helps to improve communication clarity compared to ECB's press releases. In particular, the Bulletins contain useful clarifying information on individual inflation factors and the overall forecast risk; in contrast, the bulletin's communication on monetary shocks has a negative, albeit small, impact on clarity.